The Evolution of International Human Rights Norms: A Doctrinal Study of United Nations Legal Instruments - Sherena Anodhea Eka Pramudita; Qolbi Hanif Fadhlulloh (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The evolution of international human rights norms represents a dynamic intersection of law, policy, and institutional practice, wherein the United Nations serves as both norm-maker and supervisory authority. This doctrinal study examines primary and secondary legal sources, including treaties, optional protocols, General Assembly resolutions, Human Rights Council outputs, and treaty body interpretations, alongside scholarly monographs and travaux préparatoires, to trace the historical development and thematic expansion of human rights obligations. Employing textual, contextual, and teleological interpretation pursuant to Articles 31 and 32 of the Vienna Convention on the Law of Treaties, the research identifies patterns of continuity, modification, and normative innovation, highlighting the integration of emerging domains such as climate justice, corporate accountability, refugee protection, mental healthcare, and gender equality. The study further analyzes supervisory mechanisms, interpretative guidance, and cross-instrument harmonization that reinforce legal coherence and operational legitimacy. Findings indicate that thematic expansion, coupled with institutional oversight, consolidates the UN human rights framework while accommodating contemporary global challenges. This research contributes both theoretically and methodologically by providing a systematic, normatively grounded account of the evolution, integration, and practical relevance of United Nations human rights norms.